PENINGKATAN LITERASI KEUANGAN UNTUK MENCAPAI FINANCIAL FREEDOM BAGI MASYARAKAT BANYUWANGI - Embuningtiyas, Sandra Sukma; Millati, Izzato; Puspasari, Oktaviani Rita (Nindikayla Institute, 2023)
Global economic conditions in 2024 are predicted to be in a stagnant position and tend to lead to a weakenes of the economy. In response to this problem, it is hoped that people can start preparing their finances well. One way for someone to have good finances is to do financial planning, with financial planning it will be easier for someone to survive and achieve financial freedom. Financial freedom is not only about how one can control money but about building ways to protect oneself. This community service program is carried out as an effort to provide education and insight into the importance of having healthy finances in order to create a prosperous Banyuwangi society. Methods for implementing activities include preparation, implementation and evaluation. The results of this activity are increased knowledge and awareness of financial planning as well as increasing the ability to plan ideal and healthy finances.